Models of human capital development in single-industry towns of East Kazakhstan - Yessengeldin, B.; Dauletova, A.; Serikova, G.; Daniyarova, M. (BUKETOV BUSINESS REVIEW, 2019)
The development of single-industry towns is one of the most actual problems of Kazakhstan nowadays, the solution of which can give a good impetus to the recovery of the economy not only in some regions, but also in the country as a whole. Analysis of human capital is the most important factor in the development of modern innovative economy, ensuring the development of the economy and society, including human resources, their knowledge, tools of intellectual and managerial labor, habitat and labor activity, ensuring the effective and rational functioning of human capital as a productive factor of development. In this context, issues related to the maintenance and development of human capital have priority, the potential of which should be fully utilized in the framework of industrial-innovative and integration development of individual regions and the country as a whole. The article presents the results of assessing the prospects of human capital of singleindustry towns of East Kazakhstan region in the conditions of industrial-innovative and integration development of Kazakhstan. Within the framework of the selected models of development of single-industry towns, general directions of development and support of private initiative and small business in the territory of a single-industry municipality are proposed.